The number of P-vertices in a matrix with maximum nullity - Fernandes, Maria do Rosário Silva Franco (2019)
Let T be a tree with n >= 2 vertices. Set 8(T) for the set of all real symmetric matrices whose graph is T. Let A is an element of S(T) and i is an element of {1, . . . , n}. We denote by A(i) the principal submatrix of A obtained after deleting the row and column i. We set m(A) (0) for the multiplicity of the eigenvalue zero in A (the nullity of A). When m(A(i)) (0) = m(A) (0) + 1, we say that i is a P-vertex of A. As usual, M(T) denotes the maximum nullity occurring of B is an element of S(T). In this paper we determine an upper bound and a lower bound for the number of P-vertices in a matrix A is an element of S(T) with nullity M(T). We also prove that if the integer b is between these two bounds, then there is a matrix E is an element of S(T) with b P-vertices and maximum nullity. (C) 2018 Elsevier Inc. All rights reserved.